Clinical potential of boron neutron capture therapy for locally recurrent inoperable previously irradiated head and neck cancer. (December 2015) - Lim, Diana; Quah, Daniel SC; Leech, Michelle; Marignol, Laure
Abstract: This review compares the safety and efficacy of boron neutron capture therapy (BNCT) in the treatment of previously irradiated, inoperable locoregional recurrent HNC patients and compares BNCT against the standard treatment of platinum-based chemotherapy. Our analysis of published clinical trials highlights efficacy of BNCT associated with mild side effects. However, the use of BNCT should be explored in stratified randomised trials. Highlights: BNCT can prolong median overall survival. BNCT can be associated with severe adverse effects. BNCT may be comparable to chemotherapy-based regimens. BNCT may be comparable to re-irradiation techniques regimens in patients with low performance status.